The human long noncoding RNA lnc‐IL7R regulates the inflammatory response. Issue 7 (5th June 2014) - Cui, Huachun; Xie, Na; Tan, Zheng; Banerjee, Sami; Thannickal, Victor John; Abraham, Edward; Liu, Gang
<x xml:space="preserve">Abstract</x> Long noncoding RNAs (lncRNAs), once thought to be transcriptional noise, have been recently shown to regulate a variety of biological processes. However, there is not much knowledge regarding their roles in the inflammatory response. In this study, we performed human lncRNA microarray assays and identified a number of lncRNAs that demonstrated altered expression in response to LPS stimulation. Of these lncRNAs, lnc‐IL7R, which overlaps with the 3′untranslated region (3′UTR) of the human interleukin‐7 receptor α‐subunit gene (IL7R) gene, was significantly upregulated in LPS‐treated cells. Functionally, lnc‐IL7R was capable of diminishing the LPS‐induced inflammatory response, demonstrated by elevated expression of LPS‐induced E‐selectin, VCAM‐1, IL‐6, and IL‐8 in lnc‐IL7R knockdown cells. Mechanistically, we found that lnc‐IL7R knockdown diminished trimethylation of histone H3 at lysine 27 (H3K27me3), a hallmark of silent transcription, at the proximal promoters of the inflammatory mediators. Our data suggest that lnc‐IL7R contributes another layer of complexity in regulation of the inflammatory response.